Bearing Witness 2017: Year 2 of a Pacific climate change storytelling project - David Robie (Asia Pacific Network, 2018)
In 2016, the Pacific Media Centre responded to the devastation and tragedy wrought in Fiji by Severe Tropical Cyclone Winston by initiating the Bearing Witness journalism project and dispatching two postgraduate students to Viti Levu to document and report on the impact of climate change (Robie & Chand, 2017). This was followed up in 2017 in a second phase of what was hoped would become a five-year mission and expanded in future years to include other parts of the Asia-Pacific region. This project is timely, given the new 10-year Strategic Plan 2017-2026 launched by the Secretariat of the Pacific Regional Environment Programme (SPREP) in March and the co-hosting by Fiji of the UN Framework Convention on Climate Change (COP23) climate change conference in Bonn, Germany, during November. The students dispatched in 2017 on the  ‘bearing witness’ journalism experiential assignment to work in collaboration with the Pacific Centre for the Environment and Sustainable Development (PaCE-SD) and the Regional Journalism Programme at the University of the South Pacific included a report about the relocation of a remote inland village of Tukuraki. They won the 2017 media and trauma prize of the Asia-Pacific Dart Centre, an agency affiliated with the Columbia School of Journalism. This article is a case study assessing the progress with this second year of the journalism project and exploring the strategic initiatives under way for more nuanced and constructive Asia-Pacific media storytelling in response to climate change.